Neuropathy Screening Based on Sensory Nerve Examination of Bentor Drivers in Gorontalo City: A Pilot Study - Adzani, Alviyani M.; Pateda, Sri Manovita; Jusuf, Muh. Isman; Kasim, Vivien Novarina A.; Wahjudi, Chairul (Universitas Negeri Gorontalo, 2025)
Introduction: Neuropathy, a disorder affecting the nervous system in the limbs, poses a significant concern for bentor drivers due to their occupational activities. The early detection of neuropathy through sensory nerve examinations is essential for timely medical intervention and the prevention of serious complications. This study aimed to assess the incidence of neuropathy among bentor drivers in Gorontalo City, emphasizing the urgency of addressing this issue.Method: An observational study utilizing quantitative descriptive methods was conducted in July 2024. The sample comprised 30 bentor drivers in Gorontalo City, selected through purposive sampling. Neuropathy was evaluated based on sensory nerve examinations in the lower limbs, utilizing the Neuropathy System Score (NSS) and the Neuropathy Deficit Score (NDS) questionnaires.Results: According to NSS and NDS assessments, the incidence rates of neuropathy were 73.3% and 66.6%, respectively. Most participants exhibited moderate neuropathy as indicated by NSS (30.0%) and mild neuropathy according to NDS (43.3%).Conclusion: The screening results indicate a relatively high incidence of neuropathy among bentor drivers in Gorontalo City, underscoring the necessity for early detection programs. This study advocates for further research to identify factors contributing to neuropathy within this group, engaging stakeholders in the ongoing pursuit of enhancing occupational health.Key words: Bentor driver, lower extremity, nervous system, neuropathy, occupational health